Impact of a gender and nutrition behavioral change communication amid the COVID-19 crisis in Myanmar’s Central Dry Zone - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
Social behavior change communication (SBCC) interventions on gender and nutrition are now commonly implemented, but their impact on diet quality and empowerment is rarely assessed rigorously. We estimate the impact of a nutrition and gender SBCC intervention on women’s dietary diversity and empowerment in Myanmar during an especially challenging period—the first year of the COVID-19 pandemic. The intervention was implemented as a cluster-randomized controlled trial in 30 villages in Myanmar’s Central Dry Zone. Our analysis employs data from the baseline survey implemented in February 2020 and a phone survey implemented in February–March 2021 and focuses on women’s dietary diversity and sub-indicators of the project-level women’s empowerment in agriculture index (pro-WEAI). Two indicators of women’s empowerment―inputs to productive decisions and access to and decisions over credit―improved, indicating that SBCC interventions can contribute to changing gendered perceptions and behaviors; however, most of the empowerment indicators did not change, indicating that much of gendered norms and beliefs take time to change. Women’s dietary diversity scores were higher by half a food group out of 10 in treatment villages. More women in treatment villages consumed nuts, milk, meat or fish, and Vitamin A–rich foods daily than in control villages. We show that even in the setting of a pandemic, a SBCC intervention can be delivered through a range of tools, including household visits, phone-based coaching, and voice-based training, that are responsive to local and individual resource limitations. Gender messaging can change some gendered perceptions; but it may take more time to change deeply ingrained gender norms. Nutrition messaging can help counter the declines in dietary quality that would be expected from negative shocks to supply chains and incomes.